Alterations of Mitochondrial Function and Insulin Sensitivity in Human Obesity and Diabetes Mellitus - Koliaki, Chrysi; Roden, Michael (Annual review of nutrition, 2016)
Mitochondrial function refers to a broad spectrum of features such as resting mitochondrial activity, (sub)maximal oxidative phosphorylation capacity (OXPHOS), and mitochondrial dynamics, turnover, and plasticity. The interaction between mitochondria and insulin sensitivity is bidirectional and varies depending on tissue, experimental model, methodological approach, and features of mitochondrial function tested. In human skeletal muscle, mitochondrial abnormalities may be inherited (e.g., lower mitochondrial content) or acquired (e.g., impaired OXPHOS capacity and plasticity). Abnormalities ultimately lead to lower mitochondrial functionality due to or resulting in insulin resistance and type 2 diabetes mellitus. Similar mechanisms can also operate in adipose tissue and heart muscle. In contrast, mitochondrial oxidative capacity is transiently upregulated in the liver of obese insulin-resistant humans with or without fatty liver, giving rise to oxidative stress and declines in advanced fatty liver disease. These data suggest a highly tissue-specific interaction between insulin sensitivity and oxidative metabolism during the course of metabolic diseases in humans.